ACTR-14. A PROSPECTIVE RANDOMIZED STUDY OF CONCURRENT CHEMORADIOTHERAPY WITH TEMOZOLOMIDE VERSUS RADIOTHERAPY ALONE IN PATIENTS WITH IDH WILD-TYPE/TERT PROMOTER MUTATION GRADE II/III GLIOMAS. (11th November 2019) - Liu, Yanwei; Shan, Xia; Qiu, Xiaoguang
Abstract: Our previous data showed that WHO grade II/III gliomas with isocitrate dehydrogenase wide-type (IDH-wt) and telomerase reverse transcriptase promoter mutation (TERTp-mut) have dismal prognosis as glioblastoma. This study compared concurrent chemoradiotherapy(CRT) with radiotherapy(RT) alone on the outcome of these patients. Between September 2016 and November 2018, 30 eligible grade II/III glioma patients with IDH-wt and TERTp-mut were randomly assigned to receive either RT (60 Gy in 30 daily fractions for 6 weeks) alone (n=15) or concurrent CRT with daily temozolomide and adjuvant temozolomide (n=15). The median follow-up duration was 15.5 months. The median age was 51 years (range, 24–66 years). The median Karnofsky performance status (KPS) score at randomization was 80 (range, 60–80). Surgery was the primary treatment. The characteristics of the two treatment groups were well balanced at baseline. The 1-year OS rate was significant difference between CRT group (92.3%; 95% CI: 77.8–100) and RT alone group(71.1%; 95% CI: 47.0–95.2) ( p = 0.019). Local, distant, and combined tumor recurrence patterns were observed in 4 (26.7%), 1 (6.7%), and 3 patients (20%) in the CRT group and 4 (26.7%), 3 (20%), and 3 patients (20%) in the RT alone group. Those treated with RT alone had shorter median PFS (9 vs 18 months, HR: 0.517; 95% CI: 0.193 to 1.386; p = 0.19). CRT with temozolomide and extent of resection were statistically significant predictors for survival on univariate analysis. Multivariate analysis showed that CRT was associated with a significantly better OS compared with RT alone (OR=0.195; 95% CI, 0.044 to 0.867; p =0.032). Consequently, concurrent CRT with daily temozolomide and adjuvant temozolomide for newly diagnosed IDHwt/TERTp-mut grade II/III gliomas had significantly better OS compared with RT alone. A large multi-center prospective randomized trial is warranted. The trial has been registered at ClinicalTrials.gov (NCT02766270).